Transport infrastructure: concept and content - Ustymenko , Andrii (Actual problems of law (Aktual’ni problemi pravoznavstva), 2024)
The article deals with the analysis the current legislation of Ukraine, international legal acts and works of scholars on the essence and content of the concept of «transport infrastructure». It is noted that rethinking and consolidating the concept of «transport infrastructure» at the legislative level is becoming not only relevant, but also an urgent task in the context of restoration of damaged transport infrastructure and the need to modernize and adapt the existing transport system to the standards of sustainable development and introduction of the latest technologies. The analysis of the current legislation of Ukraine and international legal acts made it possible to conclude that today the concept of «transport infrastructure» is not enshrined, and there is no consensus among scholars on the understanding of the concept of «transport infrastructure». It is noted that today the legal acts contain the concepts of «engineering and transport infrastructure», «infrastructure of a transport facility», «inland waterway transport infrastructure», «railway transport infrastructure», «port infrastructure facilities», «public railway transport infrastructure», which indicates a fragmented approach to legal regulation and indicates the need to consolidate a more unified concept of «transport infrastructure». It is suggested that the concept of «transport infrastructure» should be understood as a set of facilities, structures and components which ensure the functioning and operation of various modes of transport and constitute a single transport system of the State. It is proved the necessity of adopting a new Law of Ukraine and consolidating the concept of «transport infrastructure» in the article «Definition of Basic Concepts», which will lead to the elimination of the use of different concepts in regulating relations arising in the course of operation of various modes of transport.